2011
DOI: 10.1245/s10434-011-1635-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Cytologic Atypia in Indeterminate Thyroid Fine-Needle Aspirate Biopsies

Abstract: Background Fine-needle aspiration (FNA) biopsies are the most accurate method for diagnosis of thyroid nodules. Unfortunately, biopsies are indeterminate 15–30% of the time and surgery is thus required for a definitive diagnosis. We aimed to determine whether specific descriptors of cytologic atypia mentioned in indeterminate FNA reports were associated with malignancy on final histopathology. Methods Retrospective review of 1000 surgery patients identified 466 indeterminate FNA lesions that underwent either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Moreover, the PoM may change over time in response to practice changes and availability of molecular marker testing. It is also critical to recognize that the NPV and PPV should really be individualized for each nodule as other factors such as the sonographic appearance or the cytological features might also impact the pretest PoM (17,18,19). Although our results with the seven-gene oncogene panel might not be applicable to other institutions, miRInform performed better on follicular neoplasms than on HCN or Bethesda III samples, for which it might have limited utility.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, the PoM may change over time in response to practice changes and availability of molecular marker testing. It is also critical to recognize that the NPV and PPV should really be individualized for each nodule as other factors such as the sonographic appearance or the cytological features might also impact the pretest PoM (17,18,19). Although our results with the seven-gene oncogene panel might not be applicable to other institutions, miRInform performed better on follicular neoplasms than on HCN or Bethesda III samples, for which it might have limited utility.…”
Section: Discussionmentioning
confidence: 92%
“…This heterogeneity would be expected to impact not only the PoM but also the histological findings at the time of surgery probably causing significant differences on test performance among institutions. If comparable performance of these tests is desired among centers, the inclusion and exclusion criteria of the Bethesda III category need to be better defined and probably need to be subcategorized to improve risk stratification (17,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, a CND is typically only performed on patients with Bethesda III or IV nodules if there is macroscopic suspicion of lymph node metastases (either on preoperative imaging or intraoperatively). In addition, the presence of particularly worrisome features of cytologic atypia on the preoperative FNA of Bethesda III nodules such as nuclear grooves and/or inclusions often compel us to perform a prophylactic CND, since our group has shown that the presence of these two atypical features increases the risk of malignancy to 80% 13 . This explains why 15% of patients with Bethesda III or IV nodules underwent a CND.…”
Section: Discussionmentioning
confidence: 99%
“…A CND is typically only performed for Bethesda III and IV nodules if there are grossly suspicious lymph nodes identified on preoperative imaging or intraoperatively, or if there were particularly worrisome features of cytologic atypia (i.e. nuclear grooves or pseudo inclusions) on the preoperative FNA, which impart a significantly greater risk of malignancy 13 . Cancer recurrence was defined as a rise in serum markers (thyroglobulin and anti-thyroglobulin antibodies) and/or appearance of suspicious findings on imaging studies, which warrant clinical intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Such nodules are thereby categorized as a “follicular lesion of undetermined significance/atypia of undetermined significance (Bethesda category III).”6 This is a very heterogeneous group with an overall risk of malignancy ranging from 20% to 60% 26‐30. Our group recently demonstrated that not all descriptors of atypia confer an equal risk of malignancy; the presence of nuclear grooves, pseudoinclusions, or both, increases the risk of malignancy to 55%, 65%, and 79%, respectively 31…”
Section: Introductionmentioning
confidence: 99%